Fishery and biometrics of genus Calappa crabs (Brachyura: Calappidae) in northeastern Venezuela. - Alió, José J. (2005)
The box crabs, genus Calappa, are important crab species landed by the industrial trawl fleet in Venezuela. These crabs have a wide distribution in the country, from the Gulf of Venezuela to the Orinoco River, but major landings take place in such gulf, near Margarita Island and northern Sucre State. Average annual landing in the eastern region was 69 t during 1970-2001, with a maximum of 221 t. For this study a sample of 2 398 box crabs was collected by observers on board of industrial trawl vessels, which operated in eastern Venezuela from 1994 to 2000. Three species were found in the landings, Calappa sulcata and C. flammea, each represented 47% of the sample, and C. nítida, which accounted for 5% of the sample. Sex ratio was strongly biased towards males in C. sulcata (2.8:1) and in C. flammea (1.9:1), while it was only slightly biased in C. nitida (1.4:1). Due to its large size, C. sulcata is of great commercial interest, with average weight 290 g and a maximum weight of 720 g; C. flammea showed an average weight of 140 g and a maximum weight of 418 g, while C. nitida is the smallest species, with average weight 46 g and maximum weight not beyond 113 g. Box crabs were captured by day and night in similar proportions, and were found in a wide depth range, from a few meters to 126 m deep; however, the largest captures were obtained in the interval 38 - 54 m. Regressions between weight of chelae and total weight were linear, and significantly different between sexes. The relation between total weight and carapace width was allometric, with a power exponent ca. three in C. sulcata, and less than three in C. flamea and C. nítida. Females of C. sulcata and C. nitida showed power exponents significantly smaller than males. Since claws are removed from the animal to be commercialized, while the rest of the animal is returned alive to the sea, for practical purposes a common equation among species and sexes to convert claws weight into total body weight is: total weight = 3 x claws weight. The relationship between catch per unit of effort (CPUE) and effort did not show a significantly decreasing trend, but landings follow the effort trend, with a decreasing tendency in recent years. No mature females were found in any of the three species, thus there could be reproductive migrations towards deeper waters from October to January, when abundance of crabs is lower in the study area. It is recommended that the practice of exploiting only one claw, returning the rest of the animal alive to the sea, should be promoted among fishers, while the removal of claws from female crabs should be avoided